Individual and mixtures of metal exposures in associations with biomarkers of oxidative stress and global DNA methylation among pregnant women. (April 2022) - Zhang, Min; Liu, Chong; Li, Wen-Ding; Xu, Xue-Dan; Cui, Fei-Peng; Chen, Pan-Pan; Deng, Yan-Ling; Miao, Yu; Luo, Qiong; Zeng, Jia-Yue; Lu, Ting-Ting; Shi, Tian; et al.
Abstract: Background: Prenatal exposure to metals has been linked with adverse pregnancy outcomes. Oxidative stress and epigenetic changes are potential mechanisms of action. Objectives: We aimed to examine the associations of individual and mixtures of metal exposures with oxidative stress and DNA methylation among pregnant women. Methods: We measured a panel of 16 metals and 3 oxidative stress biomarkers including 8-hydroxydeoxyguanosine (8-OHdG), 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA) and 8-isoprostaglandin F2α (8-isoPGF2α) in urine from 113 pregnant women in a Chinese cohort. Biomarkers of global DNA methylation including Alu and long interspersed nucleotide element-1 (LINE-1) in cord blood were measured. Multivariable linear regression and Bayesian kernel machine regression (BKMR) models were separately applied to estimate the associations between individual and mixtures of metal exposures and biomarkers of oxidative stress and global DNA methylation. Results: In single-metal analyses, we observed positive associations between 11 metals [arsenic (As), cadmium (Cd), thallium (Tl), barium (Ba), nickel (Ni), vanadium (V), cobalt (Co), zinc (Zn), copper (Cu), selenium (Se) and molybdenum (Mo)] and at least one of oxidative stress biomarkers (all FDR-adjusted P -values < 0.05). In mixture analyses, we found positive overall associations of metal mixtures with 8-OHdG and 8-isoPGF2α, and Se was the most important predictor. There was no evidence on associations of urinary metals as individual chemicals and mixtures with Alu and LINE-1 methylation. Conclusion: Urinary metals as individual chemicals and mixtures were associated with increased oxidative stress, especially Se. Graphical abstract: Image 1 Highlights: Multiple urinary metals were individually associated with increased oxidative stress. The mixture of 16 urinary metals was associated with increased oxidative stress. Among 16 metals, selenium was the most contributor for increased 8-OHdG and 8-isoPGF2α. No associations were observed between urinary metals and global DNA methylation.